2009
DOI: 10.1097/sla.0b013e31819ed943
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Femoral Hernia Repair

Abstract: Femoral hernias are more common in women and lead to a substantial over risk for an emergency operation, and consequently, a higher rate of bowel resection and mortality. Femoral hernias should be operated with high priority to avoid incarceration and be repaired with a mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
97
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(104 citation statements)
references
References 19 publications
5
97
1
Order By: Relevance
“…Despite the fact that femoral hernias account for only 2-4% of all groin hernias, their timely and correct diagnosis is vital due to the increased mortality associated with emergency surgery for their complications (3). This, however, is not always easy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that femoral hernias account for only 2-4% of all groin hernias, their timely and correct diagnosis is vital due to the increased mortality associated with emergency surgery for their complications (3). This, however, is not always easy.…”
Section: Discussionmentioning
confidence: 99%
“…Gangrene was associated with an increased risk in mortality, consistent with other studies that have examined emergent general surgeries, 19 22 but obstruction was not associated with increased mortality within this inpatient population. Previous studies have shown that higher mortality from ED admissions is related to more clinically emergent presentations 1 , 23 . Our analysis adjusted for the presence of such hernia complications as obstruction and gangrene as potential confounders to allow comparison of patients with similar clinical severity between ED admission and elective repairs requiring postoperative inpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is that in emergency cases often bowel or omentum is resected due to strangulation which is an environment which would increase the risk of mesh infection, if peritonitis or an abscess especially is apparent [2]. Mesh repair has been shown to have a reduced recurrence rate compared with primary suture repair in the elective setting with no significant differences found in the emergency setting [1, 5]. Increased recurrence has been found in femoral hernias compared to inguinal hernias and emergency compared to elective cases [1].…”
Section: Discussionmentioning
confidence: 99%
“…Mesh repair has been shown to have a reduced recurrence rate compared with primary suture repair in the elective setting with no significant differences found in the emergency setting [1, 5]. Increased recurrence has been found in femoral hernias compared to inguinal hernias and emergency compared to elective cases [1]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation